Semantic Web Services for Multi-Agent Systems Interoperability - Canito, Alda (2021)
Agent-based technologies are often used including existing web services. The outputs of some services are also frequently used as inputs for other services, including other MAS. However, while agent-based technologies can be used to provide services, these are not described using the same semantic web technologies web services use, which makes it difficult to discover, invoke and compose them with web services seamlessly. In this paper, we analyse different agent-based technologies and how these can be described using extensions to OWL-S. Additionally, we propose an architecture that facilitates these services’ usage, where services of any kind can be registered and executed (semi-)automatically.